Students’ Perception on Song As Media in Learning EFL - Darman Pangaribuan; Chairunnissa (Journal of Classroom Action Research, 2023)
Despite a sizable body of research, the benefits of employing songs for learning (learner-centered) receive little attention. The purpose of the study is to understand what Indonesian EFL students think about the benefits of utilizing music to learn a new language. Eleven college students majoring in English were used to gather data for an in-depth interview approach used to investigate the research phenomena utilizing a qualitative case study design.The results of this study revealed an intriguing finding: the participants felt that using songs could help them learn English more effectively in aspects such as speaking and listening skills, pronunciation and vocabulary advancement, and development of confidence while keeping the class mood and concentration. Therefore, it is advised that songs be used in both EFL instruction by teachers and EFL instruction by students. Keywords: English Songs, Students Perception, Teaching media